LANGUAGE DEVELOPMENT IN EARLY CHILDHOOD INSPIRED BY HALLIDAY’S APPROACH: A PSYCHOLINGUISTIC PERSPECTIVES - Syahida Atika Rosliana; I Ketut Suardana; Komang Astiari; I Putu Eka Suardana (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
Psycholinguistics examines the cognitive and neurological mechanisms underlying language acquisition, comprehension, and production. In early childhood, these processes are influenced by cultural and pedagogical contexts. Halliday’s approach provides a rich environment where linguistic growth is inseparable from creativity and social interaction. This study employed a qualitative, phenomenological design, observing children in halliday’s-inspired classrooms. Data were collected through storytelling, role-play, and multimodal communication, supported by introspection and thematic analysis. The results show that children’s language acquisition is shaped by situation (observable behaviors), culture (norms of respect and reciprocity), and ideology (beliefs about agency and identity). Role-play and storytelling enhanced vocabulary and narrative competence, while multimodal communication supported meaning-making and identity formation. Language acquisition is not linear but relational and embodied. Psycholinguistic theory explains the mechanisms of comprehension and production. This manuscript brings positive impact for Psycholinguistics and teaching researches which can be used as refferences for the following teaching and psycholinguistics researches